PENGARUH KETERAMPILAN DAN FASILITAS TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN KEPEGAWAIAN DAN PEMBERDAYAAN SUMBER DAYA MANUSIA KABUPATEN MAJENE - M. Dakhri (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to: 1) describe the effect of skills on employee performance at the Office of the Agency for Personnel and Human Resources Empowerment Majene Regency, 2) describe the influence of facilities on employee performance at the Office of the Agency for Personnel and Human Resources Empowerment Majene Regency and 3) explain which variables dominant influence on employee performance at the Office of the Agency for Personnel and Human Resources Empowerment Majene Regency. The research which was conducted from September to December 2021 at the Office of the Personnel and Human Resources Empowerment Agency of Majene Regency was a research with a quantitative approach. The population taken is all employees, totaling 50 people. Because the population does not exceed 100 people, so the sample from the study is the entire population. The research was analyzed using SPSS. The results showed that 1) skills had a significant effect on the performance of employees of the Majene Regency Personnel and Human Resources Empowerment Agency, 2) facilities had a significant effect on the employee performance of the Majene Regency Civil Service and Human Resources Empowerment Agency and 3) More Dominant Facilities had a significant effect on Employee Performance of the Majene Regency Personnel and Human Resources Empowerment Agency.